2019
DOI: 10.1097/sla.0000000000003386
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Congenital Diaphragmatic Hernia After Extracorporeal Membrane Oxygenation Cannulation

Abstract: Objective: To determine the optimal timing of congenital diaphragmatic hernia (CDH) repair after extracorporeal membrane oxygenation (ECMO) cannulation Summary Background Data: The timing of CDH repair after ECMO cannulation remains a controversial topic due to studies with low power or strong selection bias. Methods: This is a 2-aim retrospective cohort study based on the CDH Study Group registry for the period of 2007-2017. Aim 1-Compare On versus After ECMO repair. Aim 2-Compare Early versus Late repair on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…Gentili et al found a stabilization interval of 43.9 ± 38.7 hours (range 22e168 hours) before patients underwent surgical correction [37]. It is possible that the lack of a standardized treatment protocol before surgical repair might contribute to infant mortality within the first week of life [35,38].…”
Section: Discussionmentioning
confidence: 99%
“…Gentili et al found a stabilization interval of 43.9 ± 38.7 hours (range 22e168 hours) before patients underwent surgical correction [37]. It is possible that the lack of a standardized treatment protocol before surgical repair might contribute to infant mortality within the first week of life [35,38].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who undergo surgical repair while on ECMO, early repair could not only reduce ECMOassociated bleeding risk at the time of repair but could theoretically permit earlier compensatory lung growth while resting on ECMO, although outcomes have been mixed [6,[11][12][13]. Robertson et al found that survival was not significantly different between those repaired before and after 5 days following cannulation at 43.3% and 41.2%, respectively [6].…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, for those patients needing ECMO, repair after ECMO is preferred [5][6][7][8]; however for highrisk patients, repair on ECMO is often necessary to minimize the risk of non-repair, allow for compensatory lung growth, and improve the chance of survival [9,10]. The optimal timing of CDH repair on ECMO, whether early or late after cannulation, is yet to be established; however, published reports to date suggest benefit with early repair [6,[9][10][11][12][13]. In a recent study, Dao et al reported that for centers that perform mostly on ECMO repairs, mortality is improved with early repair on ECMO when compared to repair after weaning from ECMO [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations